Pengaruh Inovasi Layanan Dan Kesesuaian Prinsip Syariah Terhadap Kepercayaan Nasabah Pada Bank Syariah Indonesia Cabang Pattimura - Selvi Aulia; Efni Anita; Rohana (Program Studi Ekonomi Syariah, Fakultas Ekonomi dan Bisnis Islam, Universitas Al Hikmah Indonesia, 2025)
This study aims to analyze the influence of service innovation and compliance with sharia principles on customer trust at Bank Syariah Indonesia (BSI) Pattimura Jambi Branch. The study is motivated by the importance of customer trust as a key factor in maintaining sustainable relationships between banks and customers amid the increasingly competitive Islamic banking industry. Service innovation has become one of the strategic efforts undertaken by banks to improve service quality through the utilization of digital technology, while compliance with sharia principles represents the fundamental characteristic distinguishing Islamic banks from conventional banks. Therefore, both factors are assumed to play a significant role in shaping and enhancing customer trust in Islamic banking institutions.This research employed a quantitative approach with a causal associative design. The population consisted of all customers of Bank Syariah Indonesia Pattimura Jambi Branch, while the sample comprised 100 respondents selected through purposive sampling. Data were collected using questionnaires based on a Likert scale and analyzed using the Statistical Package for Social Sciences (SPSS). The data analysis techniques included validity tests, reliability tests, classical assumption tests, multiple linear regression analysis, t-tests, F-tests, and coefficient of determination (R²).The results indicate that service innovation has a positive and significant effect on customer trust at Bank Syariah Indonesia Pattimura Jambi Branch. Furthermore, compliance with sharia principles also has a positive and significant effect on customer trust. Simultaneously, service innovation and compliance with sharia principles significantly influence customer trust. These findings suggest that customer trust is formed through a combination of innovative service quality and the bank’s commitment to consistently implementing Islamic principles. Therefore, Bank Syariah Indonesia should continue to develop technology-based service innovations while strengthening the implementation of sharia principles in order to enhance customer trust and maintain competitiveness in the Islamic banking industry